2021
DOI: 10.47947/ijnls.840322
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Analyses of Vicia L. (Fabaceae) Taxa Growing in the Southeastern Anatolia Region Based on Chloroplast TrnL Sequences

Abstract: In the current study, some natural Vicia L. taxa growing naturally in the Southeast Anatolia Region were investigated from the point of view of molecular phylogenetic. For this purpose, transfer ribonucleic acid Leucine (trnL) was sequenced in order to study the phylogenetic relationships of the Vicia L. species. Lathyrus inconspicuous L. var. inconspicuous and Lathyrus cassius Boiss. were used as an outgroup. The length of the trnL area was determined approximately as 269-534 bp. The trnL sequences were submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A cpDNA matK analysis study of Tekpinar et al (2016) reported Astragalus nezaketiae together with Astragalus czorochensis Kharadze, Astragalus humillimus, Astragalus sanguinolentus and Astragalus schizopterus species. Kaplan et al (2021a) in their cpDNA trnL intron UPGMA analysis determined Vicia sativa subsp. sativa, Vicia sativa subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cpDNA matK analysis study of Tekpinar et al (2016) reported Astragalus nezaketiae together with Astragalus czorochensis Kharadze, Astragalus humillimus, Astragalus sanguinolentus and Astragalus schizopterus species. Kaplan et al (2021a) in their cpDNA trnL intron UPGMA analysis determined Vicia sativa subsp. sativa, Vicia sativa subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Vicia L. belongs to the Fabaceae family and is the third largest family of flowering plants worldwide, containing about 210 species, with 22 divisions in two subgenera (Vicia and Vicilla), distributed throughout the temperate regions of Europe, Asia, and North and South America. In Turkey, 64 species, 22 subspecies, and 18 varieties of this genus have been recorded (Han et al, 2021b;Kaplan et al, 2021a, Kaplan et al, 2021b. The highest specific diversity of Vicia is found in Turkey and northwest Asia (Martin et al, 2018).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%